ОРГАНИЗАЦИЯ АКАДЕМИЧЕСКОГО ИЗДАТЕЛЬСТВА В СИБИРИ Документальные страницы истории (1957-1958 гг.) (Библиосфера)
The documents discussed reflect a complex and contradictory process of organizing a regional academic publishing during the early years of the Siberian Branch of the Academy of Sciences.